Dampak Media Sosial terhadap Pemahaman Keagamaan Generasi Z: Tantangan bagi Pendidikan Islam - Ayu Yulianti; Wasehuddin; Fandy Adpen Lazzavietamsi; Rifyal Ahmad Lugowi; Subhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This paper issue will become a discussion about understanding Islam from the Generation Z point of view as the first generation who have been introduced to digital technology. The important aspects relevant to information of religion in social media; positif and negative. One of the utilities of social media is that it provides insights into diverse perspectives of Islam, but when information becomes unverified, it can contribute to misunderstanding or even radicalisation.” This research is qualitative using literature study method to analyze social media impact on generation Z religious understanding. The results indicate that social media is an effective means to deepen religious knowledge provided it is moderated by sound digital literacy. So, educating strategies as well as strengthening digital literacy based on religious was seen as the main solution in optimizing the use of social media to develop a more comprehensive understanding of religion for Generation Z.